Modular two-step Access to π-extended naphthyridine systems: potent building blocks for organic electronics - Stuck, Fabian; Dietl, Martin C.; Meißner, Maximilian; Sebastian, Finn; Rudolph, Matthias; Rominger, Frank; Krämer, Petra; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2022)
Efficient synthetic approaches for the incorporation of nitrogen into polyaromatic compounds (PACs) in different patterns as stabilising moiety for π-extended systems and modification tool for optoelectronic properties remain a challenge until today. Herein, we developed a new versatile pathway to napthyridine-based PACs as non-symmetric and regioisomeric pendant to pyrazine-based PACs. A combination of a gold-catalysed synthesis of 2-aminoquinolines and the development of an in situ desulfonation and condensation of these precursors are the key steps of the protocol. The shape and type of attached functional groups of the PACs can be designed in a late stage of the overall synthetic procedure by the chosen anthranile and backbone of the ynamide introduced in the gold-catalysed step. Single-crystal X-ray diffraction and the investigation of electronic properties of the compounds show the influence of the attached substituents. All naphthyridine-based PACs show halochromic behaviour implying their use as highly sensitive proton sensor in non-protic solvents.